Diagnostic and therapeutic process of neurofibromatosis type 1 and type 2 - Michał Leśniewski; Iwona Welian-Polus; Izabela Oleksak; Karolina Maliszewska (Journal of Education, Health and Sport, 2024)
Neurofibromatosis is one of the most common genetic diseases. It is inherited in an autosomal dominant manner. It is divided into two genetically distinct subtypes, characterised by multiple skin lesions and tumours of the peripheral and central nervous system.